2015
DOI: 10.1172/jci82871
|View full text |Cite
|
Sign up to set email alerts
|

Saturated phosphatidic acids mediate saturated fatty acid–induced vascular calcification and lipotoxicity

Abstract: R e s e a R c h a R t i c l e 4 5 4 4jci.org Volume 125 Number 12 December 2015 IntroductionVascular calcification is a major complication in patients who are aging, have diabetes, or have chronic kidney disease (CKD) and is an active process that differentiates vascular smooth muscle cells (VSMCs) into osteoblast-like cells (1, 2). This process is highly regulated by transcription factors involved in osteogenic differentiation, such as RUNX2, MSX2, and ATF4 (3-5). Several in vitro and in vivo studies have sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 73 publications
5
83
0
Order By: Relevance
“…To investigate whether global ATF4 deficiency affects medial calcification, global ATF4-deficient mice were generated by backcrossing to DBA/2J mice, which are susceptible to aortic medial calcification (10,30). Since ATF4 biallelic KO mice on DBA/2J background are embryonic lethal, we used ATF4-haplodeficient (Atf4…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To investigate whether global ATF4 deficiency affects medial calcification, global ATF4-deficient mice were generated by backcrossing to DBA/2J mice, which are susceptible to aortic medial calcification (10,30). Since ATF4 biallelic KO mice on DBA/2J background are embryonic lethal, we used ATF4-haplodeficient (Atf4…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we recently reported that the saturated fatty acid stearic acid strongly induces vascular calcification through ER stress (9,10). We then determined whether saturated fatty acids induce the expression of PiT1 and C/EBPβ.…”
Section: C/ebpβ Regulates Mineralization and Pit1 And Pit2 Expressionmentioning
confidence: 99%
See 3 more Smart Citations